Hydrogen Bond Assisted l to d Conversion of α‐Amino Acids. Issue 11 (31st January 2020) - Fu, Rui; So, Soon Mog; Lough, Alan J.; Chin, Jik
Abstract: l to d conversion of unactivated α‐amino acids was achieved by solubility‐induced diastereomer transformation (SIDT). Ternary complexes of an α‐amino acid with 3, 5‐dichlorosalicylaldehyde and a chiral guanidine (derived from corresponding chiral vicinal diamine) were obtained in good yield as diastereomerically pure imino acid salt complexes and were hydrolysed to obtain enantiopure α‐amino acids. A combination of DFT computation, NMR spectroscopy, and crystal structure provide detailed insight into how two types of strong hydrogen bonds assist in rapid epimerization of the complexes that is essential for SIDT. Abstract : l to d conversion of unactivated α‐amino acids was achieved by solubility‐induced diastereomer transformation (SIDT). Ternary complexes of an α‐amino acid with 3, 5‐dichlorosalicylaldehyde and a chiral guanidine were obtained in good yield as diastereomerically pure imino acid salt complexes and were hydrolyzed to obtain enantiopure α‐amino acids. Detailed insight into how two types of strong hydrogen bonds assist in rapid epimerization of the complexes is provided.